Measurement of Impedance by Cross-Coupler and Sliding Short at Microwave Frequencies - Misra D. (My University, 2025)
A technique for measuring the impedance at microwave frequencies using cross-coupler and a sliding short has been described in this paper. The theory behind the measurements is given and it has been shown that this arrangement is a complete substitute of the slotted line technique. Copyright © 1978 by The Institute of Electrical and Electronics Engineers, Inc.